The Impact of Critical Listening and Critical Reading on Critical Thinking - Yasemin Baki (Behavioral Sciences, 2025)
Critical listening, critical reading, and critical thinking are three closely related cognitive skills that aim to evaluate information with an analytical and questioning approach. Critical listening and critical reading, which are receptive language skills, represent the application of critical thinking in different contexts. Critical thinking, which is a productive language skill, provides a framework for these two receptive language skills and enables the evaluation of the accuracy of information accessed through critical listening and critical reading, analyzing different perspectives and making inferences to reach correct conclusions. These two skills support the development of critical thinking skills and contribute to individuals gaining deeper understanding based on the perspective of knowledge. This study aims to determine the relationships between critical listening, critical reading, and critical thinking, the effects of these variables on each other, and the explanation ratios. The study group of this study was determined through simple random sampling, one of the random sampling methods. The participants consisted of 201 teacher candidates studying in the Department of Turkish Language Teaching at a university in the north of Türkiye. The Critical Listening Scale, Critical Thinking Attitude Scale, Critical Reading Self-Efficacy Perception Scale, and a personal information form were used to collect research data. The data collected in the research were analyzed using structural equation modeling via AMOS 22.0. As a result of the research, it was determined that all hypothesis models established based on the relevant literature were valid. Two of the three hypotheses regarding the theoretical model were supported by the data, and one hypothesis was rejected. Critical listening has a direct high level effect on critical thinking and predicts it at a significant level. Critical listening has a direct high-level effect on critical reading and predicts it at a significant level, while explaining 65% of the total variance related to critical reading. The effect of critical reading on critical thinking is insignificant and does not predict critical thinking at a significant level. In the theoretical model created the effect of critical reading on critical thinking is insignificant, but these two variables explain 85% of the variance related to critical thinking. As a result of the research, it can be said that the main predictor of critical thinking is critical listening, and that critical reading and critical thinking develop depending on the development of critical listening.